New Archaeological Discoveries in The Geological Formations and Heritages along the Ba River Ancient Valley - Phuc, La The; Tuat, Luong Thi; Thom, Bui Van; Su, Nguyen Khac; Duc, Vu Tien; Anh, Bui Quang; Minh, Nguyen Trung; Hai Yen, Dang Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 36 No 3, 2020)
In dry season of 2019, a series of new mix-heritages containing both of natural/geological and prehistoric archaeological values were discovered along the Ba river ancient valley by the field survey team of the project TN17/T06. The archaeological relics were uncovered right in the geological heritage sites such as: waterfalls, fossil sites, ancient terraces, and low mountain slopes along the Ba river ancient valley, which belong to eluvial, deluvial, proluvial and alluvial formations of Pleistocene age. Hundreds of stone tools, including dozens of petrified wood tools were collected, such as: uni-facial and bi-facial tools, end-chooper, side-chopper, scraper, spearhead tool, flake and core tools, etc. The materials of the tools were made of quartz, quartzite, siliceous stone, opal-chalcedony, petrified wood and basalt, which were recognized as geological heritages (A type: Paleontology; D type: Rock; F type: Minerals, according to the classification in the Circular 50/2017-TT-BTNMT of MONRE) of the heritage region. The collected artifacts characterise technique and geometric shape types of Paleolithic age. The archaeological discoveried sites were highly evaluated by Vietnamese and foreign archaeologists because they play a great important role in studying Paleolithic stage in Gia Lai province and The Central Highlands particularly, and in Vietnam and Southeast Asia generally. Besides, they have increased comprihensive heritage values of the region, as well as provided double invaluable resources (both natural and cultural heritage) for tourism exploitation and socio-economic sustainable development.